A Review of: “Islamic State in Africa: The Emergence, Evolution, and Future of the Next Jihadist Battlefront” by Jason Warner, Ryan O’Farrell, Héni Nsaibia, and Ryan Cummings - Nwankpa, Michael (Journal of Central and Eastern European African Studies, 2024)
A Review of: “Islamic State in Africa: The Emergence, Evolution, and Future of the Next Jihadist Battlefront” by Jason Warner, Ryan O’Farrell, Héni Nsaibia, and Ryan Cummings